Tratamiento de aguas residuales mediante sistemas de zanjas y pozos de infiltración para el sitio san jacinto, canton santa rosa. - Pintado Alvarado, Andrés Byron (2017)
The present work aims to design a wastewater treatment system by means of ditches and infiltration wells for the San Jacinto site of the Santa Rosa canton and to solve the problem of insalubrity that causes the contamination of the affluents of the sector due to the Lack of pre-treatment to domestic wastewater, in this site, as in most rural areas there is no treatment plant that purifies domestic sewage, as a result, residents of the sector are forced To discharge these waters to the nearest tributaries, this project proposes two alternatives based on absorption systems. The purpose of this study and the main focus of the project is to determine, based on the results of the infiltration tests carried out at the site where the treatment is to be implemented, an efficient and low cost construction, operation and maintenance alternative, taking advantage of To the maximum the characteristics of the soil of the place. To do this, the respective field and laboratory tests were carried out. In what corresponds to field work, infiltration tests were carried out at different depths in order to determine the infiltration rate of each stratum present in that soil, the results of these Tests determined that the soil of this site is favorable for the implementation of a system that contemplates ditches and infiltration wells as an alternative of wastewater treatment of the sector at secondary level. In addition, in order to propose a complete prototype, pre-treatment of wastewater at primary and primary level is implemented. Each system will have a treatment at the preliminary level by means of a roughing grid to guarantee the greater retention of solids present in these waters and at primary level it is proposed the use of a septic tank that will act as settler of floating particles, with this Tank is intended to eliminate a large amount of pollutants present in the water. As a secondary treatment, infiltration ditches will be used in the first proposal, the same ones that were calculated with the data obtained from the infiltration tests, specifically with the infiltration rate of the terrain and the design flow obtained from the population data and the dams, these ditches will form an infiltration field in order to receive the water from the previous treatments to infiltrate them on the ground and conclude with the treatment process. It should be emphasized that in this system it will be possible to take advantage of the infiltration fields as seedlings of timber trees in order to have a profitability by the end of the useful life of the treatment system. As a second alternative, it is proposed the implementation of infiltration wells for secondary treatment, this consists of an infiltration field made up of a set of wells destined to infiltrate the previously treated waters in the field, in this project the two alternatives are analyzed Soil of the sector allows to implant taking as reference the capacity of the land to filter the water and the option that would be indicated for the sector.